Թուղթը, առօրեականությունը և հասարակական փոխակերպումները Կիլիկյան Հայաստանում - Գևորգյան, Զոհրաբ (Մատենադարան)
Throughout history, the discovery and spread of certain materials have been revolutionary in human daily life, as well as in economic, political and cultural transformations. One such material is paper, the discovery and widespread use of which brought profound changes to the world. The spread of paper, in fact, led to a unique informational revolution in the Middle Ages. It culminated in the establishment of the first printing house in Europe, which was followed by many others including the first Armenian printing house in Venice founded in 1512. The "domination" of paper continued until the late 20th century. Изобретение и распространение определенных материалов могло играть революционную роль как в повседневной жизни человека, так и в экономике, политике и культуре. Одним из таких материалов была бумага, изобретение и широкое использование которой внесло в мир глубокие изменения. Распространение бумаги, по сути, привело к уникальной информационной революции в средние века, кульминацией которой стало создание в позднем средневековье первой типографии в Европе, за которой последовало множество других типографий, в том числе первая армянская типография в Венеции, основанная в 1512 году. Бумага господствовала со средневековья до 20 века.
Keywords: Առևտուր